Potential application of rLc36 protein for diagnosis of canine visceral leishmaniasis - Camila Tita Nogueira; Mayara Lúcia Del Cistia; Ana Carolina Urbaczek; Márcia MG Jusi; Angela Maria Arenas Velásquez; Rosângela Zacarias Machado; Henrique Ferreira; Flávio Henrique-Silva; Hélio Langoni; Paulo Inácio da Costa; Márcia AS Graminha (Memorias do Instituto Oswaldo Cruz)
Visceral leishmaniasis (VL) is fatal if left untreated. Infected dogs are important reservoirs of the disease, and thus specific identification of infected animals is very important. Several diagnostic tests have been developed for canine VL (CVL); however, these tests show varied specificity and sensitivity. The present study describes the recombinant protein rLc36, expressed by Leishmania infantum, as potential antigen for more sensitive and specific diagnosis of CVL based on an immunoenzymatic assay. The concentration of 1.0 μg/mL of rLc36 enabled differentiation of positive and negative sera and showed a sensitivity of 85% and specificity of 71% (with 95% confidence), with an accuracy of 76%.